A review of the use of geophysics in base- and precious-metal exploration - Furnell, R G (Rhodes University, Faculty of Science, Department of Geology, 1981)
The object of geophysical surveys in mineral exploration has traditionally been to detect subsurface geological features, which may reflect the presence of mineralization in depth and, if possible, to measure the dimensions of the causative body. Geophysical methods may also be used to locate extensions to known mineralization and for determining the size, depth and internal characteristics of an orebody. Marked improvements in geological concepts of ore genesis have led to a better appreciation, amongst geologists, of mineralized environments, and this has had an effect on the use of geophysics in recent years. Geophysical surveys are being increasingly used as an aid in environmental reconstructions and the results of regional surveys may be used to provide an indirect guide to ore. One of the main applications of geophysics lies in areas where the orebodies and associated structures are not exposed, as most geophysical measurements are more expensive than surface geological or geochemical surveys.
Keywords: Geophysics; Geological surveys; Precious metals; Mining geology